Design of Packaging for Microballoon Actuators and Feasibility of their Integration within Aerodynamic Flight Vehicle - Linga Murthy, A.; Krishna, Y.; Murti, V.S.R. (Defence Science Journal, 2009)
The microballoon actuators are used for the active flow control in turbulent boundary layer for aerodynamic control of flight vehicles. The packaging, interfacing, and integration of the microballoon actuators within the flight vehicle play a key role for functioning of the microballoon actuators during the flight conditions. This paper addresses the design and analysis of packaging and integration aspects and associated issues. The use of microballoon actuators on the control surfaces and nose cone of flight vehicles has the positive influence of delaying the flow separation from the aerodynamic surface. This results in enhancing aerodynamic effectiveness and lift as well as reduction of drag. A typical control surface is configured with eight microballoon actuators symmetric wrt the hinge line of the control surface and embedded within the control surface. Provision of the Pneumatic feed line system for inflation and deflation of the microballoons within the control surface has been made. The nose cone has been designed to have 32 such actuators at the circular periphery. The design is found to be completely feasible for the incorporation of microballoon actuators, both in the nose cone and in the control surface. Defence Science Journal, 2009, 59(5), pp.485-493, DOI:http://dx.doi.org/10.14429/dsj.59.1549